Kimberly Saye: capstone - Saye, Kimberly, artist (Colorado State University. Libraries, 2013)
The artist's statement: My visual interests tend to lean towards vibrant, cool colors and subtle patterns. I also make my works bold and stand out, as well. My point of view as an artist is to create works that are pleasing to the eye and set a calming and relaxed mood to the environment in which they are placed. When I research textiles and fibers, I enjoy the aesthetics that are seen in functional items. This is why all of my pieces are functional. When planning my works, I sometimes have dreams about what I brainstorm; these dreams help lead me to very concrete ideas and plans. Somewhere between asleep and awake, my mind allows me to recognize ideas that my fully conscious mind does not, and I am inspired to create functional art with a colorful dream-flair.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers